Recurrent Abdominal Aortic Aneurysm After Aortoiliac Endograft Stent Placement - Alexandra J. Toloczko; Seher Berzingi; Benjamin V. Bailey; Lubna B. Wani; Mayada H. Issa (Annals of Internal Medicine: Clinical Cases)
We report a case of a 59-year-old man with multiple comorbid conditions who had endovascular aortic repair for an abdominal aortic aneurysm (AAA). Despite the procedure's initial success, the patient later presented with recurrent AAA as the result of an enlarged aneurysmal sac and a 90-degree angle kink at the midportion of the endograft stent, necessitating emergent open surgery. This case underscores the challenges in managing AAA post endovascular aortic repair and the potential for serious complications. Our experience highlights the importance of close surveillance and prompt intervention for optimal patient outcomes.